(untitled) (Ta’limning zamonaviy transformatsiyasi, 2024)
ANNOTATION: The dictionary has long been an essential tool for understanding and mastering language. Over time, dictionaries have evolved from printed tomes to digital applications, reflecting shifts in how people seek information and interact with language. This article examines the history of dictionary use, explores the changes brought by technology, and evaluates the dictionary's modern role in education, research, and everyday life. By comparing past and present use, the article sheds light on the transformation of dictionaries and their enduring significance.